The burden of multiple myeloma: assessment on occurrence, outcomes and cost using a retrospective longitudinal study based on administrative claims database (Italian Journal of Public Health, 2011)
Objective: Multiple myeloma (MM) is a malignancy of plasma cells that results in an overproduction of light and heavy chain monoclonal immunoglobulins. Multiple myeloma imposes a significant economic and humanistic burden on patients and society. The present study is aimed at assessing the burden of multiple myeloma in both epidemiologic and economic terms.Methods: A retrospective, naturalistic longitudinal study on the occurrence, outcome and cost of multiple myeloma using an administrative database, was performed. We selected residents of a North-eastern Region of Italy, who had their first hospital admission for multiple myeloma during the period 2001-2005. This group was followed up until 31-12-2006, death or transfers to other regional health services. Direct medical costs were quantified within the perspective of the Regional Health Service.Results: During the period 2001-2005, out of a population if 1.2 million inhabitants, we observed 517 incidents of patients diagnosed with MM (52% female). During the period of observation, 364 (70.4%) subjects died. Total health care costs per patient over the maximum of follow-up were estimated to be 76,630 Euro for subjects younger than 70 years old and 22,892 Euro in the older group.Conclusions: Multiple myeloma imposes a significant epidemiological and economic burden on the healthcare system.
Keywords: Administrative database; cost; incidence; multiple myeloma